2014
DOI: 10.1063/1.4860943
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the first-to-second order magnetic phase transformation on the transport properties of La0.7Ca0.3−xBaxMnO3 compounds

Abstract: We studied the influence of the magnetic phase transition on the transport properties of La0.7Ca0.3−xBaxMnO3 compounds with x = 0.05, 0.075, and 0.10. Our experimental results demonstrated the ferromagnetic-paramagnetic and metal-insulator transitions taking place at temperatures TC = 265–300 K and TMI = 280–310 K, respectively, which increase with increasing Ba-doping content. While the x = 0.05 sample undergoes a first-order magnetic phase transition (FOMT), x = 0.10 undergoes a second-order magnetic phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These compounds have a disadvantage that their Curie temperatures, T C ($270 K) are well below room temperature. However, partial substitution of Ca by larger sized ions like Sr, Ba and Pb could lead to an increase in T C and an enhancement in MCEs is seen in these compounds [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have a disadvantage that their Curie temperatures, T C ($270 K) are well below room temperature. However, partial substitution of Ca by larger sized ions like Sr, Ba and Pb could lead to an increase in T C and an enhancement in MCEs is seen in these compounds [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1(b)(d)), whereas the LCBMO bulk sample undergoes a FOPT. 5) In addition, Franco and Conde 17) suggested that the overlap of all the ¦S m (T ) curves into a unique curve is an additional confirmation of the general validity of the treatment in SOPT materials. From these reasons, clearly, the samples with D = 3957 nm are SOPT materials, while the sample with D = 79 nm is located in between the FOPT and SOPT materials (i.e., the crossover of the first-to-secondorder phase transformation).…”
Section: Resultsmentioning
confidence: 97%
“…These values are slightly lower than T C obtained for the LCBMO bulk/asprepared sample (³265 K). 5) Clearly, the D reduction did not change the T C significantly, but broadened the FM-PM phase transition region. The phase-transition width determined from the full-width-at-half maximum of the dM/dT versus T curve increases from 12 to 17 K with decreasing D from 79 to 39 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations